2015
DOI: 10.4149/bll_2015_056
|View full text |Cite
|
Sign up to set email alerts
|

The decrease in NKG2D+ Natural Killer cells in peripheral blood of patients with metastatic colorectal cancer

Abstract: Abstract:Background: Natural killer (NK) cells play important roles in the immune defense against tumors such as colorectal cancer. In humans, NKG2D is an activating immune receptor constitutively expressed in most cytotoxic lymphocytes including NK and CD8+ T cells. In this study, the expression of NKG2D molecule was investigated in peripheral blood NK cells from colorectal cancer patients and compared with healthy subjects. Methods: We studied 21 non-metastatic (low-grade), 17 non-metastatic (high-grade), 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Mtb infection was not found to decrease the NKG2D expression of CD8 + T cells. However, in cancer models, the decreased expression of NKG2D both on CD8 + T and on NK cellular surfaces was demonstrated, and it was determined to be a mechanism that compromises cell function and promotes tumor immune escape . Regarding human CD56 + CD8 + T cells, it has been demonstrated that this subpopulation is less vigorous in terms of proliferation, after which it is bound to classical class I HLA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mtb infection was not found to decrease the NKG2D expression of CD8 + T cells. However, in cancer models, the decreased expression of NKG2D both on CD8 + T and on NK cellular surfaces was demonstrated, and it was determined to be a mechanism that compromises cell function and promotes tumor immune escape . Regarding human CD56 + CD8 + T cells, it has been demonstrated that this subpopulation is less vigorous in terms of proliferation, after which it is bound to classical class I HLA.…”
Section: Discussionmentioning
confidence: 95%
“…However, in cancer models, the decreased expression of NKG2D both on CD8 + T and on NK cellular surfaces was demonstrated, and it was determined to be a mechanism that compromises cell function and promotes tumor immune escape. 26,27 Regarding human CD56 + CD8 + T cells, it has been demonstrated that this subpopulation is less vigorous in terms of proliferation, after which it is bound to classical class I HLA. This subpopulation displays enhanced natural cytotoxicity activity and cytokine secretion, and it was proposed that the frequency of CD56 + CD8 + T cells could be affected by cytomegalovirus infection and aging.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are innate immune-effector cells involved in tumor surveillance (10,53,54); however, the functionality of NK cells is altered in patients with cancer (8,10,54), showing reduced degranulation capability and cytotoxicity. Despite their low numbers in TUMs, the presence of CRC infiltrating NK cells can influence patient outcome (14,(55)(56)(57). A significant down-regulation of several activatory receptors, including CD16, NKG2D, NKp30, NKp44, NKp46, CD161, and DNAM-1, has been observed in CRC circulating and tissue-infiltrating NK cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…NK cell was generally scarce within CRC tumor tissues, on the contrary, normal level of NK cell was examined in adjacent normal mucosa [ 39 ]. Meanwhile, a significant reduction in the percentage of NKG2D+NK cell was observed in peripheral blood of metastatic colon cancer patients [ 40 ]. Additionally, tumor-associated macrophage (TAM) is one of the most frequently found immune cells in the tumor microenvironment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%